RESPON TANAMAN JAGUNG TUMPANGSARI KACANG HIJAU TERHADAP PERLAKUAN PARIT PADA LAHAN KERING - Edy Edy; Tohari Tohari; Didik Indradewa; Dja’far Shiddieq (JURNAL AGROTROPIKA, 2011)
Water management in rainfed drylands are very important to consider. Limited water on dry land can be anticipated with rain harvesting technologies such as by making the trench. To further optimize land with soil moisture, maize intercropping with mungbean. This study aims to determine the effectiveness of trench system with intercropping maize with mungbean. The research was conducted in Village of Wareng, sub District of Wonosari District of Gunungkidul Province of D.I. Yogyakarta, during November 2010 until February 2011. This study was designed using the Randomized Split Plot. The main plot is a trench system consists of three types: Without a trench (Control, P0), the Trench (P1), the Trenches+organic material (P2). Subplot is the cropping pattern consists of two types: Corn monoculture (J) and mungbean intercropping maize (J + H). Maize tested were Bima-2 Bantimurung varieties most resistant to drought conditions based on previous research. The results showed that the combination of trench + organic materials and intercropping patterns can increase maize leaf area index about 40%. The yield obtained maize intercropped with mungbean on the treatment of trench + organic materials with about 6.258 ton ha-1 of corn and 0.418 ton ha-1 of mungbean while in the trench treatment without organic material 4.829 t.ha-1 of corn and mungbean 0.369 ton ha-1. Efficiency of water use in intercropping maize and mungbean increased about 60.8%; Intercropping maize and mungbean in the treatment of trench + organic materials and trench without organic material increased the land equal ratio about 76.05% and 40.70% respectively. Key words: trench, intercropping, maize, mungbean, dryland.